1992
DOI: 10.1177/036354659202000510
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of meniscal injury associated with acute anterior cruciate ligament injury in skiers

Abstract: To determine if the incidence and patterns of meniscal injury associated with acute anterior cruciate ligament injury in skiers are different from those seen in individuals injured in nonskiing athletic activities, we reviewed the records of 150 patients with acute anterior cruciate ligament injuries. All patients had undergone arthroscopic evaluation within 21 days from the time of injury. There were 75 individuals who were injured while skiing and 75 individuals who sustained an injury in some other high-loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 37 publications
4
50
0
Order By: Relevance
“…In an acute ACL tear of the valgus, the rotational force compressing the lateral compartment makes lateral meniscal tears more common [4,10,14]. The injury triad of ACL-MCL-lateral meniscus appeared twice as often as the ACL-MCL-medial meniscus combination.…”
Section: Discussionmentioning
confidence: 99%
“…In an acute ACL tear of the valgus, the rotational force compressing the lateral compartment makes lateral meniscal tears more common [4,10,14]. The injury triad of ACL-MCL-lateral meniscus appeared twice as often as the ACL-MCL-medial meniscus combination.…”
Section: Discussionmentioning
confidence: 99%
“…Although other authors have found a somewhat lower incidence of horizontal tears, most agree that this type of tear constitutes a significant portion of degenerative tears of the meniscus (1 1, 13,17,26,27,37). Although radial fiber sheets are thought to prevent traumatic longitudinal tears in the meniscus (4,8,9), they actually may predispose the meniscus to horizontal tears.…”
Section: Figmentioning
confidence: 98%
“…This finding regarding the torsion release is of great importance because it is known that in both, recreational as well as competitive skiing, the largest number of injuries is related to the lower extremities, particularly to the knee joint [12][13][14]. For the knee joint it was found that both, internal and external rotations of the ski, are associated with knee injury mechanisms [22][23][24].…”
Section: Discussionmentioning
confidence: 96%